Operation Joktan - Tsarfati, Amir; Yohn, Steve ([Eugene, Oregon] : Harvest Prophecy, an imprint of Harvest House Publishers, 2021)
Nir Tavor is an Israeli secret service operative turned talented Mossad agent.Nicole le Roux is a model with a hidden skill.A terrorist attack brings them together, and then work forces them apart--until they're unexpectedly called back into each other's lives.But there's no time for romance. As violent radicals threaten chaos across the Middle East, the two must work together to stop these extremists, pooling Nicole's knack for technology and Nir's adeptness with on-the-ground missions. Each heart-racing step of their operation gets them closer to the truth--and closer to danger.In this thrilling first book in a new series, authors Amir Tsarfati and Steve Yohn draw on true events as well as tactical insights Amir learned from his time in the Israeli Defense Forces. For believers in God's life-changing promises, Operation Joktan is a suspense-filled page-turner that illuminates the blessing Israel is to the world.
Keywords: Intelligence officers -- Fiction; Terrorism -- Fiction; Christian fiction; Israel -- Fiction; Middle East -- Fiction; Spy fiction; Action and adventure fiction; Thrillers (Fiction)